Batman '89 : echoes - Hamm, Sam (DC Comics, 2025)
"Batman '89: Echoes is the follow-up to the Batman '89 graphic novel, continuing the adventures of the Dark Knight from Tim Burton's classic movie Batman. YOU WANNA GET NUTS? LET'S GET NUTS! After Harvey Dent's crusade against Gotham and Batman, the Caped Crusader has disappeared without a trace. In his place, ordinary citizens have taken to the streets to root out crime. As innocents get hurt, the question on everyone's mind is the same: Where is Batman? Sam Hamm, screenwriter of the 1989 Batman movie, and Joe Quinones reunite for another tale in Gotham!"-- Provided by publisher.